(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the importance of emotional intelligence in the development of interpersonal relationships during adolescence. Emotional intelligence refers to the ability of a person to understand and manage their own emotions as well as recognize the emotions of others. Particularly during adolescence, this ability plays a significant role in social adaptation, effective communication with peers, and personal development